The Dynamics of Four-Species Ecological Model - Naji, Raid; Saady, Rami (Iraqi Journal of Science, 2023)
In this paper, a four species mathematical models involving different types of ecological interactions is proposed and analyzed. Holling type – II functional response is a doubted to describes the behavior of predation. The existence, uniqueness and boundedness of the solution are discussed. The existences and the stability analysis of all possible equilibrium points are studied. suitable Lyapunov functions are used to study the global dynamics of the system. Numerical simulations are also carried out to investigate the influence of certain parameters on the dynamical behavior of the model, to support the analytical results of the model.